PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS AUGMENTED REALITY PADA MATA PELAJARAN PERENCANAAN DAN PENGALAMATAN JARINGAN DI SMK MUHAMMADIYAH 1 PADANG - Marbun, Aisyah; Darni, Resmi; Marta, Rizkayeni; Huda, Yasdinul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by students’ limited understanding of network topology material due to the continued use of conventional learning media, such as textbooks, PowerPoint presentations, and lecture-based methods that lack interactivity. Additionally, the use of educational technology to present material in a visual and engaging manner has not yet been optimized. This study aims to develop valid, practical, and effective Augmented Reality (AR)-based interactive learning media using the Assemblr Edu platform for Network Topology material. The method used is Research and Development (R&D) based on the ADDIE model, which includes Analyze, Design, Development, Implementation, and Evaluation. Data were collected through observations, interviews, questionnaires, and tests. The results of the media validation by three validators yielded scores of 4.76, 4.80, and 4.70, categorized as “Highly Valid,” while the content validation yielded scores of 4.91, 4.82, and 4.82, also categorized as “Highly Valid”. The practicality test results showed a score of 4.73, categorized as “Highly Practical,” while the effectiveness test yielded an N-Gain value of 0.87 (87%), categorized as “Highly Effective”. Based on these results, the Augmented Reality based learning media developed has been proven to be valid, practical, and effective, making it suitable for use in enhancing students’ understanding of network topology material.